Efficiency of Drip Irrigation in Intensive Orchards - Miroyan, S. A. (ՀԱԱՀ հիմնադրամ)
Technical and economic efficiency of the drip irrigation for intensive orchards has been justified by the example of Nor Artamet community in the Kotayk region. The working principle of drip irrigation system, its performance indices, as well as crops irrigation regime applied in the intensive orchards has been investigated and collated with the same indices recorded in the traditional orchards irrigated through surface irrigation method. It has been proved that the vegetation period in the intensive orchards cultivated through drip irrigation is distinguished by high economic indices and profitability. Thus, the latest irrigation technologies definitely ensure development of intensive agriculture.
Keywords: Agricultural Engineering